Obesity and Systemic Inflammation: Pathophysiological Mechanisms and Management Strategies - Ayesha Abdul Raoof (Oral Sphere Journal of Dental and Health Sciences, 2026)
The worldwide increase in the prevalence of obesity marks the beginning of the global public health crisis that it unparalleled in human history. Obesity is the second major public health problem after tobacco use. Obesity is the central problem underlying the other epidemics of chronic diseases such as cardiovascular diseases, type 2 diabetes, and non-alcoholic fatty liver disease. Obesity is the key underlying problem. The systemic and chronic inflammation fuels the associated co-morbid conditions and obesity itself. I will devote the remainder of this review to the mechanistic aspects of the systemic inflammation induced by obesity. I will begin with the primary source: the adipose tissue itself, and expansion of the fat tissue, and infiltrating immune cells, along with the various forms of insulin resistance. Then I will review the evidence of the adipocytes' secretion of pro-inflammatory and inflammation perpetuating cytokines and adipokines as the central activators of the chronic and systemic fuel to the metabolic dysfunction of inflammation. The exit of the obesity and inflammation cycle needs a management plan. The lifestyle changes targeting diet and physical activity focus on the inflammation axis and assist in fat mass decline, along with the use of some prescribed anti-inflammatory medications, and drugs such as GLP-1 agonists and SGLT-2 inhibitors. For patients with severe morbid obesity, the impact of immune-modulating fat mass reduction and bariatric surgery and gastric bypass is chronic and systemic. This review highlights the importance of integrating lifestyle modifications, medications, and surgical options in the management of obesity and inflammation to optimize health outcomes and mitigate the complications associated obesity.